MO732HD-PATIENTS WITH ATRIAL FIBRILLATION TREATED ADEQUATELY AND SAFE WITH DOAC BY INDIVIDUAL DOSING USING ROUTINE ANTI-XA DRUG-EFFECT MONITORING: LONG-TERM CLINICAL PRACTICE DATA. (29th May 2021) - Brensing, Karl August; Raab, Peter; Heidkamp, Peter; Pöge, Uwe
Abstract: Background and Aims: Hemodialysis (HD) patients (Pts) with nonvalvular atrial fibrillation (AF) on anti-vitamin-K oral anticoagulation (VK-OAC) are at high risk for cardio-vascular events, major bleeding and rapid vascular/valvular calcification. Thus, current VK-OAC is debated since prospective studies are missing, but all direct oral anticoagulation drugs (DOACs) are not labeled for ESRD. We studied the clinical feasibility of long-term DOAC treatment in HD-pts using individual dosing by regular anticoagulant drug-effect monitoring. Method: We analysed 9 HD-patients with AF (median age 77 yrs; range=R: 59-86; 7 Male) on DOAC therapy for at least 6 months (n=1 rivaroxaban=Riva, n=8 apixaban=Apix) initiated by cardiologist with patients informed consent with lower dose as in CKD-4 under regular (weekly) anti-Xa drug-effect monitoring (prior HD) using available routine laboratory test validated for low-molecular heparin: Target trough range (12-24h after drug) was 0.1-1.0 U/ml (=prophylactic to therapeutic anti-Xa levels; test range <0.1, >1.6 U/ml). Bleeding caused drug stop/reduction until anti-Xa control. Results: Median study time was 14 months (R: 6-24). We analysed 310 anti-Xa levels on Apix and 83 levels on Riva. After dose adjustment finally 2 Apix-Pts (22%) received full CKD-4 dose (35 mg/week=wk) and 7 patients (78%) had median dose of 10 mg/wk (10-27 mg; 6x Apix) or 40 mg/wk Riva, i.e. 29% and 38% of usual CKD-4 dose. Two Pts with higher dose had clinical reasons: short-bowl-syndrome (less resorption) or high grade (3-4) left atrial sludge (therapeutic goal). Overall, median anti-Xa level was 0.47 U/ml (R: <0.1->1.6) and 80% were in center-accepted targets: 0.1-1.2 U/ml. Lower dose Pts had higher in-target-rate (83%) than the 2 high dose Pts (70%) by more exceeding the upper limit. During our study we saw no cerebral/systemic thrombo-embolic event or major bleeding, but 2 pts had epistaxis (need out-patient intervention), 1x persistent macrohematuria (need catheterization) and 3 pts. had multiple subcutaneous hematoma, none needed event-related transfusion. We saw two non-cardiovascular deaths (22%; 2/9): 1x pneumonic sepsis, 1x advanced cancer. Conclusion: We provide new clinical feasibility data on long-term DOACs therapy in HD-patients. Since DOACs are not labelled for ESRD we recommend strict indication plus regular anti-Xa drug-effect monitoring for adequate individual dosing. Our data support initial doses as for CKD-4 but applied only on HD-free days (4x/wk; =57% of usual) and adjustment in steady-state (1-2 wks): final individual doses were increased up to 100% in some patients, but mostly were reduced to 30-40% of usual CKD-4 doses. Overall, this individual dosing approach for DOACs provided adequate anti-Xa levels to prevent thrombo-embolic as well as major bleeding events. This initial data need to be confirmed in larger studies to improve evidence-based management of HD-patients with nonvalvular AF.